Effect of freezing and drying methods on some biochemical properties of prickly fig (Opuntia ficus-indica) fruit - Çakmak, Meltem; Bakar, Büşra; Ibrahim, Muhammad Salihu; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (Centenary University, 2020)
In this study, the fruit of Opuntia ficus-indica was examined in the fresh, frozen, sun and in microwave dried samples. In fresh Opuntia ficus-indica samples, the total phenolic and flavonoid content was found to be 3.30 µg GAE/g DW and 1.46 µg QE/g DW, whereas in sun-dried samples found to be 2.60 µg GAE/g DW and 0.56 µg QE/g DW respectively. TEAC and IC50 are indicators of antioxidant capacity, and in fresh fruits TEAC and IC50 found to be 66.91 µmol Trolox/g DW and 45.95 mg ml-1, while 39.01 µmol Trolox/g DW and 57.36 mg ml-1 in sun-drying, respectively (p<0.05). While the amount of ghrelin, GSH, GSSG and MDA in fresh prickly fig were found to be 19.20; 372; 20.85; 3.00 µg/g DW, on the other hand in sun-dried samples were found to be 9.90; 210.00; 33.60; 4.78 µg/g DW, respectively. In addition, ghrelin and GSH in dried fruits decreased while GSSG and MDA increased in comparison to fresh sample (p<0.05). It can be concluded that the fruit of Opuntia ficus-indica is rich in ghrelin and GSH. The most suitable preservation techniques for Opuntia ficus-indica fruits is freezing to consume it in all season and microwave drying appears to be more advantageous than sun-dried in terms of time. © 2020, Centenary University. All rights reserved.
Dondurma ve kurutma yöntemlerinin dikenli incir (Opuntia ficus-indica) meyvesinin bazı biyokimyasal özellikleri üzerine etkisi
Keywords: Antioxidant capacity; Conservation methods; Glutathione; Opuntia ficus-indica; Phenolic substances